2021
DOI: 10.1097/rli.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iterative Denoising 3-Dimensional T2-Weighted Turbo Spin Echo for the Diagnosis of Deep Infiltrating Endometriosis

Abstract: ObjectivesThe primary end point of this study was to evaluate the image quality and reliability of a highly accelerated 3-dimensional T2 turbo spin echo (3D-T2-TSE) sequence with prototype iterative denoising (ID) reconstruction compared with conventional 2D T2 sequences for the diagnosis of deep infiltrating endometriosis (DIE). The secondary end point was to demonstrate the 3D-T2-TSE sequence image quality improvement using ID reconstruction.Material and MethodsPatients were prospectively enrolled to our ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…4,12 Previous works demonstrated the usefulness of denoising methods in abdominopelvic MRI for improvement of image quality and compensation of SNR loss. [13][14][15][16] Furthermore, it was most recently shown that deep learning (DL) techniques exhibit much potential for improvement of MR image quality and drastic reduction of acquisition time in abdominopelvic MRI. [17][18][19] The most recent developments of DLbased superresolution algorithms including partial Fourier acquisition allow to retrospectively omit portions of the acquired data mimicking a more aggressive partial Fourier setting including theoretical acquisition time reduction of the reconstructed images.…”
mentioning
confidence: 99%
“…4,12 Previous works demonstrated the usefulness of denoising methods in abdominopelvic MRI for improvement of image quality and compensation of SNR loss. [13][14][15][16] Furthermore, it was most recently shown that deep learning (DL) techniques exhibit much potential for improvement of MR image quality and drastic reduction of acquisition time in abdominopelvic MRI. [17][18][19] The most recent developments of DLbased superresolution algorithms including partial Fourier acquisition allow to retrospectively omit portions of the acquired data mimicking a more aggressive partial Fourier setting including theoretical acquisition time reduction of the reconstructed images.…”
mentioning
confidence: 99%
“…Another study comparing the image quality and reliability of 3D SPACE with ID and conventional 2D T2w for the diagnosis of deep infiltrating endometriosis determined that the ID algorithm significantly improved the image quality compared with 3D T2w (p < 0.001). One reader found a significant improvement in image quality compared with 2D T2w (p < 0.01), while the other reader found no difference (11).…”
Section: Discussionmentioning
confidence: 86%
“…The combination of SPACE acquisition with CAIPIRI-NHA acceleration (27,28), reconstructed using a prototype ID algorithm, demonstrated remarkable results in several body and musculoskeletal applications, including the uterus (11,19,29). 3D SPACE with ID was shown to be beneficial by generating a solitary set of volumetric T2w images with the opportunity for multiplanar reconstructions, thus eradicating the risk of false slice orientation (11). Moreover, the acquisition time of 3D SPACE with ID was shorter than that of separately acquired multiple stBLADE orientations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, T 2 ‐weighted imaging is a time‐consuming component of the prostate MRI examination, typically involving repeated acquisitions with signal averaging in order to obtain a sufficient signal‐to‐noise ratio for interpretation. Denoising approaches 7,8 can improve the subjective perception of image quality when combined with shorter acquisitions, and in some scenarios have been shown to allow for equivalent performance of diagnostic tasks compared to longer acquisitions without denoising 9–14 . However, any postprocessing method targeted to improving measures of image quality must be investigated to determine whether they alter the diagnostic assessment of images, either positively or negatively.…”
mentioning
confidence: 99%